Study on Combustion Processes of a Premixed Charge Compression Ignition (PCCI) Engine Fueled with DME/Diesel. Issue 1 (January 2021) - Zhao, Yuwei; E, Weibo; Niu, Tianlin; He, Jiangjiang
Abstract: A dimethyl ether (DME) pre-mixing system was installed on a 2105 diesel engine for realizing pre-mixed charge compression ignition combustion mode. Combustion processes of a PCCI engine fueled with DME/diesel under various DME pre-mixing ratios were investigated in this paper. The results showed that the heat release process showed three stages with port induction of DME. As the DME pre-mixing ratio (PR) increased, the peak value of cylinder temperature and pressure raised and the corresponding crank angles advanced. The start of combustion (SOC) moved forward obviously and the duration of combustion extended; the peak value of the pressure rise rate reduced first and then raised. The results in this paper provided a reference for the combustion process optimization of DME/diesel PCCI engine.